2016
DOI: 10.1002/ece3.1777
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effects as drivers of sibling competition in a parent–offspring conflict context? An experimental test

Abstract: Maternal effects occur when the mother's phenotype influences her offspring's phenotype. In birds, differential allocation in egg yolk components can allow mothers to compensate for the competitive disadvantage of junior chicks. We hypothesize that the parent–older chick conflict peaks at intermediate conditions: parents benefit from the younger chick(s) survival, but its death benefits the older chick in terms of growth and survival. We thus expect maternal compensation to follow a bell‐shaped pattern in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Weather variation can, but does not always, influence maternal hormones transported into the egg, and these components can affect nestling growth (Schwabl, 1996;Groothuis et al, 2005;Addison et al, 2008;Groothuis and Schwabl, 2008;Ruuskanen et al, 2016). In particular, weather impacts on food may have a strong effect on maternal hormones deposited in the egg and could aid the matching of brood size to environmental conditions (Verboven et al, 2003;Gasparini et al, 2007;Vergauwen et al, 2012;Benowitz-Fredericks et al, 2013;Müller and Groothuis, 2013;Merkling et al, 2016). Other than hormonal influences, weather could also indirectly impact nestling growth through antioxidants, immunoglobins and antimicrobial agents (Williams, 2012), but these effects might be more indirect, as these compounds are less likely to affect growth directly and instead likely help nestlings survive in the face of environmental challenges (e.g., parasites).…”
Section: Weather Impact Of Growth Through Prenatal Effectsmentioning
confidence: 99%
“…Weather variation can, but does not always, influence maternal hormones transported into the egg, and these components can affect nestling growth (Schwabl, 1996;Groothuis et al, 2005;Addison et al, 2008;Groothuis and Schwabl, 2008;Ruuskanen et al, 2016). In particular, weather impacts on food may have a strong effect on maternal hormones deposited in the egg and could aid the matching of brood size to environmental conditions (Verboven et al, 2003;Gasparini et al, 2007;Vergauwen et al, 2012;Benowitz-Fredericks et al, 2013;Müller and Groothuis, 2013;Merkling et al, 2016). Other than hormonal influences, weather could also indirectly impact nestling growth through antioxidants, immunoglobins and antimicrobial agents (Williams, 2012), but these effects might be more indirect, as these compounds are less likely to affect growth directly and instead likely help nestlings survive in the face of environmental challenges (e.g., parasites).…”
Section: Weather Impact Of Growth Through Prenatal Effectsmentioning
confidence: 99%
“…We estimated body mass and size growth rates over 35 days by calculating the maximum slope of a logistic growth curve between morphological measures and age (Merkling et al, 2012) using the grofit package in r (Kahm, Hasenbrink, Lichtenberg-Frate, Ludwig, & Kschischo, 2010). Because such measurement necessarily excludes chicks that were not measured up to 35 days old, we also estimated growth rates over the first 10 days by calculating the slope of the linear regression between the morphological measures and age (Merkling et al, 2014(Merkling et al, , 2016).…”
Section: Morphological Measurements and Growthmentioning
confidence: 99%
“…A compensation with egg mass has been found in an altricial bird, but only during the early stages of chick development (Bitton et al 2006). The opposite has been observed in seabirds in which maternal investment in eggs (hormones or egg size dimorphism) fails to compensate for hatching asynchrony, since Merkling et al (2016) found that mothers seem to favor the competitiveness of their younger chick, in intermediate conditions of food availability, via egg yolk components, but the study also suggests that hatching asynchrony need to be small for efficient maternal compensation. In the cases where maternal effects compensate for hatching asynchrony, it is only during the early stages of growth (Reid and Boersma 1990).…”
Section: Discussionmentioning
confidence: 85%
“…Considering that the study year was ‘intermediate', and that there was an increase in investment in second eggs by females in better condition (Barrionuevo and Frere 2014), it is possible that females in good condition invest more in last chicks to enhance their competitiveness via maternal effects, for instance, by egg size dimorphism (Barrionuevo and Frere 2014). Females may also contribute to the increased growth of their last chick by differential allocation of yolk substances (Schwabl 1993, Muller and Groothuis 2012, Benowitz‐Fredericks et al 2013, Merkling et al 2016). As a result, we found a relationship between biological mother's condition and chick body size, even though they did not raise their biological chicks.…”
Section: Discussionmentioning
confidence: 99%